Why China should ratify the International Convention for the control and management of ships’ ballast water And sediments - LIU, Nengye (Institutional Knowledge at Singapore Management University, 2014)
This paper argues that China should ratify the 2004 International Convention for the Control and Management of Ships' Ballast Water and Sediments (BWM Convention) in the near future. It first briefly describes the recent development of the BWM Convention and China's position toward the BWM Convention. Then it analyzes benefits for China to ratify the BWM Convention. Some suggestions for the improvement of current legal regime on the prevention of invasive species from ballast water are provided as well.